Preparation and chemistry of an unexpectedly stable α-oxoketene-pyridine zwitterion, 2,2-bis(tert-butylcarbonyl)-1-[4-(dimethylamino)pyridinio]ethen-1-olate - Kollenz, G. (2014)
European Journal of Organic Chemistry